Western Studies of Southeast Asian Islam: Problem of Theory and Practice - John R. Bowen (Studia Islamika, 1995)
Islamic studies conducted in Southeast Asia Western observers during this tendency dominated framework which clearly separates between the teachings of Islam as a set of Islamic practices of living in society. They make the teachings of Islam as contained in the books as a benchmark to see if the Islamic community in this area or not.Such an approach would obviously not be able to capture and understand the reality of life in a Islamic society as revealed in the creative interpretation done by the scholars, naib, chaplain, and local intellectuals who actively and imaginatively connecting their ideas and local practices with the texts and traditions -broader Islamic tradition. They are developing Islamic culture in a different way. This culture mediates the "rules" or theory and "practice" their religion so that they are meaningful social life of Islam. Because it ignores the role of local interpreters famous works of Islamic Southeast Asia failed to understand the relationship between normative texts, the processes of interpretation and any behaviors that make up the reality of Islam that can be observed.DOI: 10.15408/sdi.v2i4.821